10.1002/9781118797914 (CrossRef Listing of Deleted DOIs, 2000)
BACKGROUND: In computed tomography (CT), radiation dose is commonly evaluated using system-displayed metrics such as CTDIvol; however, variations in X-ray beam quality may influence organ absorbed dose even under identical CTDIvol conditions. PURPOSE: To investigate the impact of X-ray beam quality, including tube voltage and beam-shaping filters, on organ absorbed dose in chest computed tomography (CT) under identical CTDIvol conditions, with particular emphasis on spectral characteristics and energy-dependent dose conversion. METHODS: Half-value layer (HVL) measurements were performed using the aluminum attenuation method to determine effective energy under different tube voltage conditions (80, 100, 120, and 135 kV, and 120 kV with a silver [Ag] filter). X-ray spectra were measured using a CdTe-based spectrometer with a 90°Compton scattering configuration, and mean photon energy was calculated from the measured spectra. Absorbed doses in the breast and lung were evaluated using optically stimulated luminescence (OSL) dosimeters placed in an anthropomorphic phantom. Scan parameters were adjusted to maintain a constant CTDIvol (6.2 mGy) across all conditions. Absorbed dose was calculated from air kerma using f-factors derived from both effective energy and mean photon energy. RESULTS: Effective energy increased with tube voltage and was markedly elevated by the Ag filter. Spectral measurements demonstrated substantial reduction of low-energy photons and beam hardening under the Ag condition. Despite identical CTDIvol, both air kerma and absorbed dose varied with beam quality. Absorbed dose generally increased with effective energy in both tissues; however, under the 120 kV + Ag condition, the two tissues diverged: the lung absorbed dose decreased despite the higher effective energy, whereas the breast absorbed dose continued to increase. When the mean photon energy was used instead, this discrepancy was resolved differently: the absorbed dose decreased under the 120 kV + Ag condition in both the breast and the lung. This tissue-dependent sensitivity to the choice of energy metric was attributable to the energy dependence of the f-factor, which approached or exceeded unity in the breast under the Ag condition. CONCLUSIONS: Organ absorbed dose in chest CT varies with beam quality even under identical CTDIvol conditions, and this variation is tissue-dependent. Effective energy and mean photon energy can lead to different, and in the breast even opposite, conclusions regarding the direction of dose change under the same irradiation condition. Specifically, under standard (non-filtered) conditions, mean-photon-energy-based absorbed doses in the breast were approximately 4%-5% higher than effective-energy-based estimates, whereas under the 120 kV + Ag condition this relationship reversed, with mean-photon-energy-based doses approximately 1.6% lower. Although the magnitude of this reversal was relatively small, it was consistent and reproducible across repeated measurements. These findings highlight that the choice of energy metric used to convert air kerma to absorbed dose can meaningfully affect organ dose assessment in CT dosimetry, particularly when the f-factor approaches or exceeds unity.